Representation of documents in technical communication - Rahtz, S (De Gruyter, 2012)
This chapter considers standards and models for the representation of textual content, both for the purpose of the organisation and presentation of content. It provides an overview of the characteristics and usage of most commonly used document markup formats (OOXML, Open Document Format, TeX/LaTeX, DocBook, Text Encoding Initiative (TEI), XHTML, etc.) with a view on their scope and application. A central theme of the chapter is a clarification of the notion of a document in relation to that of text. The chapter will overview issues in representing the structure, content and function of documents. Further, it reviews document formats in the light of their support of these representation tasks. It should be noted that, for convenience, this chapter deals entirely with documents and texts managed in electronic form, as is now almost universally the case. Many of the arguments would apply, however, to older analogue information as well.